2013
DOI: 10.7763/ijbbb.2013.v3.167
|View full text |Cite
|
Sign up to set email alerts
|

CheV1 Plays an Important Role in Chemotaxis of Vibrio Cholerae

Abstract: Abstract-The complete genome sequence of V. cholerae has revealed the presence of four CheV's, namely putative CheV, CheV1, CheV2 and CheV3, along with the three chemotaxis-related signaling systems designated as System I, II and III. To determine the roles of the CheV proteins, whose genes are located outside of the che gene clusters, we examined their cellular localization and then their roles in chemotaxis. Among the four CheV's, CheV1 plays a major role in chemotaxis as observed with swarm assay and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…V. cholerae has at least four cheV homologs: cheV1 (VC0395_A1207), cheV2 (VC0395_A1592), cheV3 (VC0395_1794) and putative cheV (VC0395_0285). Among them, we have assigned cheV1 to System II as overexpression of the gene interferes with swarming (Hiremath et al, 2013) and localization of CheA2(II)-GFP (data not shown). On the other hand, overexpression of any cheV homolog did not drastically disturb hypoxia-induced localization of CheA1(I)-GFP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae has at least four cheV homologs: cheV1 (VC0395_A1207), cheV2 (VC0395_A1592), cheV3 (VC0395_1794) and putative cheV (VC0395_0285). Among them, we have assigned cheV1 to System II as overexpression of the gene interferes with swarming (Hiremath et al, 2013) and localization of CheA2(II)-GFP (data not shown). On the other hand, overexpression of any cheV homolog did not drastically disturb hypoxia-induced localization of CheA1(I)-GFP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study using swarm assays and fluorescence microscopy discovered that this CheV plays a role in chemotaxis (Hiremath et al ., 2013).…”
Section: Cluster Ii/f6 Systemmentioning
confidence: 99%
“…(It is noteworthy that in this specific study cheV genes are numbered from a silent 0 instead of explicit 1: CheV(VC1602), CheV1(VC2006), CheV2(VC2202), and CheV3(VCA0954). So the labeling “CheV” used in the study (Hiremath et al ., 2013) actually refers to the same protein “CheV1” of the later study (Yang et al ., 2018).…”
Section: Cluster Ii/f6 Systemmentioning
confidence: 99%